Relationship Between The Rhythmic Activity Of The Cerebral Cortex And The Manifestation Of Impulsivity / Reflexivity - Kozachuk, Nataliia O.; Shvarts, Liudmyla O.; Zhuravlov, Oleksandr A.; Poruchynskyi, Andrii I.; Dmytrotsa, Olena R.; Abramchuk, Olha M.; Poruchynska, Tetiana F.; Zhuravlova, Olena V.; Hoshko, Liudmyla I.; Козачук, Наталія Олександрівна; Шварц, Людмила Олексіївна; Журавльов, Олександр Анатолійович; et al. (Research Journal of Pharmaceutical, Biological and Chemical Sciences, 2018)
The most significant EEG differences were obtained by us for the purpose of receiving the indicators of the coherence of the brain biopotentials in Δ-, θ-, β-frequency bands. These EEG differences were obtained in the course of performing tasks of the divergent type that are associated with the cognitive style of "impulsivity-reflexivity", which in its turn is based on the ability of an individual to make quick or slow decisions. It was established that in males, who are reflexive, the level of spatial synchronization was higher than the one of impulsive men in the Δ-, θ-, and β-frequency bands while performing the divergent task. And this was mainly achieved due to closer long-distance connections of the frontal areas of the cerebral cortex with occipital, temporal and parietal areas.
Keywords: coherence; electroencephalogram; cognitive style